2016
DOI: 10.1371/journal.pone.0159632
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Activity of MeCP2 Is Enhanced by C-Terminal Truncating Mutations

Abstract: Methyl-CpG binding protein 2 (MeCP2) is a widely abundant, multifunctional protein most highly expressed in post-mitotic neurons. Mutations causing Rett syndrome and related neurodevelopmental disorders have been identified along the entire MECP2 locus, but symptoms vary depending on mutation type and location. C-terminal mutations are prevalent, but little is known about the function of the MeCP2 C-terminus. We employ the genetic efficiency of Drosophila to provide evidence that expression of p.Arg294* (more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…This neurotoxicity is not observed when the MECP2‐E1 isoform is over‐expressed. Similar neurotoxicity has been described when human MECP2‐E2 is expressed in Drosophila (Williams et al., 2016). It may be noted that other studies have shown that in Drosophila , human MECP2 associates with chromatin, regulates transcription, and is phosphorylated at the same sites as in mammalian cells (Cukier et al., 2008).…”
Section: Mecp2 Duplication Syndrome (Mds)supporting
confidence: 71%
See 2 more Smart Citations
“…This neurotoxicity is not observed when the MECP2‐E1 isoform is over‐expressed. Similar neurotoxicity has been described when human MECP2‐E2 is expressed in Drosophila (Williams et al., 2016). It may be noted that other studies have shown that in Drosophila , human MECP2 associates with chromatin, regulates transcription, and is phosphorylated at the same sites as in mammalian cells (Cukier et al., 2008).…”
Section: Mecp2 Duplication Syndrome (Mds)supporting
confidence: 71%
“…Interestingly, loss‐of‐function mutations of FOXG1 cause a Rett‐like syndrome (previously known as congenital variant Rett syndrome), whereas duplication of the FOXG1 gene causes FOXG1 duplication syndrome or West syndrome, which like MDS, is characterized by epilepsy, motor abnormalities, and cognitive impairment (Hettige & Ernst, 2019; Hou et al., 2020; Wong et al., 2019). As observed in mammalian neurons, FOXG1 over‐expression protects against MECP2‐E2‐induced neurotoxicy in Drosophila (Williams et al., 2016). Interestingly, FOXG1 interacts with MECP‐E2 and FOXG1 expression is reduced in neurons primed to die.…”
Section: Mecp2 Duplication Syndrome (Mds)mentioning
confidence: 89%
See 1 more Smart Citation
“…91 However, phosphorylation of MeCP2 at Ser80 reduces interaction with FOXG1 and promotes apoptosis. 102 Unlike the E2 isoform, MeCP2-E1 is not bound by FOXG1 and does not promote apoptosis when overexpressed. In contrast to the regulation of MeCP2 phosphorylation, both depolarization and IGF-1 increase phosphorylation of FOXG1.…”
Section: The Close Relationship Between Cdkl5 Foxg1 and Mecp2 At The ...mentioning
confidence: 99%
“…In vivo , a human MeCP2-e2 isoform gain-of-function mutation promoted apoptosis in Drosophila motor neurons [59]. In addition, MeCP2 overexpression led to neuronal loss in the hippocampus, cortex, and cerebellum in a MeCP2 triplication syndrome mouse model [52].…”
Section: Mecp2 and Neuronal Cell Death: Apoptosis Excitotoxicity Anmentioning
confidence: 99%